How The Influence of Dynamic Communication of Adolescents to Prevent Bullying - Ratih Siti Aminah; Pudji Muljono; Djuara P. Lubis; Dwi Hastuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study investigates that adolescent communication is influenced by various factors, including individual characteristics, parents, and peers. This study aims to analyze the influence of adolescent characteristics on their communication patterns with parents and peers, examine how parental characteristics affect communication with adolescents, identify the role of peers in shaping adolescent communication patterns, and explore the relationship between adolescent interpersonal communication and the tendency toward negative behaviors such as bullying. This research employs a quantitative approach, analyzing data from 481 respondents. The findings indicate that age, gender, and birth order influence the intensity and openness of adolescent communication. Parental characteristics, including age, education, and occupation, also determine family communication patterns, with parents with higher education levels tending to have more democratic communication styles. Furthermore, peers play a significant role in shaping adolescent communication patterns and behavior, particularly in social and psychological aspects. Poor interpersonal communication with parents correlates with an increased risk of negative behaviors such as bullying. This study concludes that effective family communication and the influence of the social environment are crucial in shaping adolescent interactions.